0524 Factors Associated with Delayed Treatment of Patients with Severe Obstructive Sleep Apnea. (27th April 2018) - Jobanputra, A M; Kritikou, I; Ortiz, L; Tan, M; Simonsen, S; Epelboim, J
Abstract: Introduction: Untreated severe obstructive sleep apnea (OSA) is associated with various adverse outcomes and significant cardiovascular morbidity and mortality. Previous randomized controlled trials have demonstrated improvement in some of the cardiovascular disease factors in patients diagnosed with severe OSA when treated with continuous positive airway pressure (CPAP). In this study, we aimed to identify factors associated with delay in initiation of CPAP treatment of patients with severe OSA. Methods: Retrospective chart review analysis of patients diagnosed with severe OSA based on home sleep apnea test (HSAT) or polysomnography (PSG) in the University of Pennsylvania sleep laboratory between June to July 2017. Severe obstructive sleep apnea was diagnosed based on apnea-hypopnea index (AHI) equal to or greater than 30 events per hour. Patients were stratified into three categories: those with appropriate treatment initiated within thirty days, delay of more than thirty days in initiating appropriate therapy, and those with no treatment initiation at all. Additionally, demographic data and sleep or non-sleep medicine physician placing the sleep study order was identified. Results: Of the total of 112 adult patients diagnosed with severe OSA in June and July 2017 at the University of Pennsylvania, CPAP was not ordered for 22 patients (19.6%) and was ordered later than thirty days post-diagnosis for 19 patients (17.0%). Of the patients with no CPAP ordered, 17 patients (77.3%) had the sleep study ordered by non-sleep medicine physicians. 12 of the patients (63.2%) with CPAP ordered later than 30 days post diagnosis, had the sleep study ordered by non-sleep medicine physicians. Conclusion: Even though multiple studies have shown that untreated severe OSA is associated with various adverse outcomes and significant cardiovascular morbidity and mortality, many non-sleep medicine physicians are unaware of the different treatment modalities available. Our study demonstrated delay in treatment initiation when a sleep study is ordered by physicians not trained in sleep medicine. Evaluation by sleep physician of patients suspected for OSA may result in a timely treatment of this high-risk patient population. Support (If Any): None.